Acanthaleyrodes elevatus sp. n. (Hemiptera: Aleyrodidae) from India, with key to species and discussion of tuberculate setae - Dubey, Anil Kumar; Singh, Sudhir; Martin, Jon H. (Zootaxa, 2014)
The genus Acanthaleyrodes Takahashi is reported for the first time from India. Acanthaleyrodes elevatus sp. n. is described from Bridelia retusa in Kerala, India, with a key to puparia of Acanthaleydes species. The new species differs in its exceptionally elevated eighth abdominal tergite, circular vasiform orifice and eight pairs of subdorsal setae. The generic characteristics of Acanthaleyrodes are redefined and distinguished from those of Tuberaleyrodes Takahashi. A. styraci Takahashi is re-described in detail with illustrations of puparia and immatures from Hong Kong. A lectotype puparium is designated for A. callicarpae Takahashi. The development of tuberculate setae is discussed, in whitefly puparia and earlier nymphal instars, and considered to be subject to environmental modification.